Enhancement of anaerobic degradation of petroleum hydrocarbons by electron intermediate: Performance and mechanism. (January 2020) - Liu, Xiang; Li, Zhengwen; Zhang, Chen; Tan, Xuejun; Yang, Xue; Wan, Chunli; Lee, Duu-Jong
Highlights: A quinone-respiring strain named C8 was isolated and identified. Isolated C8 could utilize multifarious TPH with the aid of biosurfactant. AQDS accelerate the electron transfer in the degradation of TPH and nitrate. The accumulation of intermedia nitrite was eliminated and TPH removal was improved. Abstract: A quinone-respiring strain capable of degrading multitudinous petroleum hydrocarbons was isolated by selective medium and identified as Bacillus sp. (named as C8). Maximum 76.7% of total petroleum hydrocarbons (TPH) were degraded by the biosurfactant-mediated C8 with the aid of nitrate and electron intermediate (anthraquinone-2, 6-disulphonate, AQDS). The quantitative real-time PCR results of several intracellular key functional genes suggested that AQDS could participate in the transformation of intermediates and accelerate the electron transfer in the degradation of TPH and nitrate, thereby eliminating the accumulation of nitrite and increasing the degradation efficiency of TPH. A strengthening mechanism, which promoted electron transport in the anaerobic denitrification degradation of petroleum hydrocarbons by quinone-respiring strain with the aid of electron intermediate, was proposed. The influencing factors were evaluated by using response surface methodology, and the TPH removal was positively related to temperature but negatively to pH.